Cortical Thickness in Crouzon–Pfeiffer Syndrome: Findings in Relation to Primary Cranial Vault Expansion. Issue 10 (October 2020) - Wilson, Alexander T.; de Planque, Catherine A.; Yang, Sumin S.; Tasker, Robert C.; van Veelen, Marie-Lise C.; Dremmen, Marjolein H.G.; Vrooman, Henri A.; Mathijssen, Irene M.J.
Abstract : Background: Episodes of intracranial hypertension are associated with reductions in cerebral cortical thickness (CT) in syndromic craniosynostosis. Here we focus on Crouzon–Pfeiffer syndrome patients to measure CT and evaluate associations with type of primary cranial vault expansion and synostosis pattern. Methods: Records from 34 Crouzon–Pfeiffer patients were reviewed along with MRI data on CT and intracranial volume to examine associations. Patients were grouped according to initial cranial vault expansion (frontal/occipital). Data were analyzed by multiple linear regression controlled for age and brain volume to determine an association between global/lobar CT and vault expansion type. Synostosis pattern effect sizes on global/lobar CT were calculated as secondary outcomes. Results: Occipital expansion patients demonstrated 0.02 mm thicker cortex globally ( P = 0.81) with regional findings, including: thicker cortex in frontal (0.02 mm, P = 0.77), parietal (0.06 mm, P = 0.44) and occipital (0.04 mm, P = 0.54) regions; and thinner cortex in temporal (−0.03 mm, P = 0.69), cingulate (−0.04 mm, P = 0.785), and, insula (−0.09 mm, P = 0.51) regions. Greatest effect sizes were observed between left lambdoid synostosis and the right cingulate (d = −1.00) and right lambdoid synostosis and the left cingulate ( d = −1.23). Left and right coronal synostosis yielded effect sizes of d = −0.56 and d = −0.42 on respective frontal lobes. Conclusions: Both frontal and occipital primary cranial vault expansions correlate to similar regional CT in Crouzon–Pfeiffer patients. Lambdoid synostosis appears to be associated with cortical thinning, particularly in the cingulate gyri.